Characterization of interdisciplinary activities in a Colombian faculty of arts (2020)
Knowledge fragmentation separates educational organizations from reality and calls into question the legitimacy of the academic endeavors before society. This research seeks to contribute to the resolution of knowledge management problems associated with interdisciplinary work in a faculty of arts. The exploratory and descriptive study analyzes the implicit and explicit knowledge of faculty professors through the use of interviews and structured surveys. The sample was formed by 22 teachers of a Colombian university. The results show a potential interaction between team members of the faculty, suitable for exploration in project development, for which it is necessary to focus on a vision and create spaces for collective project construction from a systemic perspective